Interferon-induced transmembrane protein 3 (IFITM3) gene polymorphisms in COVID-19 patients in Assiut University Hospitals - Esraa Abdelaziz; Amany Nafeh; Ahmed Hasanein; Hytham Abdalla; Ragaa Rashwan (Microbes and Infectious Diseases)
Background and aims: Interferon-induced transmembrane protein 3 (IFITM3) plays an important antiviral role in the adaptive and innate immune response, it prevents hemifusion of the viral membrane and host cellular membrane in a broad spectrum of enveloped viruses, e.g. influenza A, ebola, marburg or SARS-CoV. This study aimed to evaluate correlation of IFITM3 gene polymorphisms (rs12252) and infection susceptibility, severity and mortality rate of COVID-19 patients. Patients and methods: The IFITM3 SNP (rs12252) polymorphism was genotyped by (RT-PCR) in 100 SARS-CoV-2-negative controls and 100 SARS-CoV-2- positive, who admitted to Chest, Assiut University and other quarantine Hospitals respectively in Assiut city, Egypt. Results: The minor allele frequency (rs12252 (G)) were significantly more frequent in the patients compared to controls after age and sex matching (p-value = 0.011, OR (95% CI) =2.44 (1.20-4.97). This allele (G) was significantly more common among patients who ICU admitted than non-ICU admitted (p -value = 0.001, OR (95% CI) =3.78 (1.64-8.75)). Also, was significantly more frequent in dead patients than cured patients (p -value = 0.005, OR (95% CI) =3.33 (1.37-8.10)). Conclusion: The present study has shown significant association between G (the mutant type) allele variant of IFITM3 rs12252 and COVID-19 infection susceptibility and disease severity and mortality.